[Letter to Samuel the doctor] - ha-Ḥazzan, Yiṣḥaq b. Ṣedaqa
Letter from Yiṣḥaq b. Sedaqa in Tripoli, Libya, to the physician Shemuel in Cairo, thanking him for his ransom when the sender was captured by the Normans in Jerba, Ifrīqiya. Yiṣḥaq writes Shemuel that he married the daughter of his paternal uncle and that his father sold their house in Jerba for ninety dinars as a result of famine and to cover debts. Dated to October 1136 based on T-S K6.47 (PGPID 8484). (Information from Mediterranean Society, III, pp. 30, 117-118, 150; IV, p. 283)
Keywords: Judaïsme -- Djerba